2017
DOI: 10.1002/jms.4030
|View full text |Cite
|
Sign up to set email alerts
|

UPLC‐QTOF‐MSE‐based diagnostic product ion filtering to unveil unstable C6‐C2 glucoside conjugates in Forsythia suspensa

Abstract: Forsythia suspensa contains C -C glucoside conjugates (CCGCs) that are chemically unstable, thereby hindering their isolation and purification. In the present study, ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF) was utilized to screen and identify unstable CCGCs in the fruits and leaves of F. suspensa without any tedious isolation and purified process based on independent information acquisition (also called MS ) and individual MS/MS experiments. Diagnostic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The backbone of C6‐C2 glucoside conjugates was glucose with two substituents, including a, b, c, d, f, g, h, i, and j, at C‐1 and C‐6 through glycosidic and/or ester linkages (Xia et al, 2017). A comparative study of their fragmentation behaviors found that there was one backbone ion at m / z 179.0550 existing in all MS/MS spectra of C6‐C2 glucoside conjugates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The backbone of C6‐C2 glucoside conjugates was glucose with two substituents, including a, b, c, d, f, g, h, i, and j, at C‐1 and C‐6 through glycosidic and/or ester linkages (Xia et al, 2017). A comparative study of their fragmentation behaviors found that there was one backbone ion at m / z 179.0550 existing in all MS/MS spectra of C6‐C2 glucoside conjugates.…”
Section: Methodsmentioning
confidence: 99%
“…The backbone of C6-C2 glucoside conjugates was glucose with two substituents, including a, b, c, d, f, g, h, i, and j, at C-1 and C-6 through glycosidic and/or ester linkages (Xia et al, 2017)…”
Section: Characterization Of C6-c2 Glucoside Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A technique based on UHPLC–Q‐TOF‐MS was introduced employing independent information acquisition named UHPLC–Q‐TOF‐MS Energy can be used to identify most compounds . It could simultaneously detect precursor ions at low collision energy and fragment ions at high energy in a single injection, and greatly improve the efficiency of composition screening and identification .…”
Section: Introductionmentioning
confidence: 99%
“…Great challenges still remain in the processing of complex multi-way data derived from LC-MS. Some approaches such as mass defect filtering [9], multiple product ion filtering [10,11], neutral loss filtering [11,12], and fragment ion diagnostic strategy [13] were developed and used to deduce parent and fragment ions. However, these data post-processing technologies developed are based on a single component and may neglect the structure correlations between chemical constituents.…”
mentioning
confidence: 99%